Sentiment analysis of German texts in finance: Improving and testing the BPW dictionary - Matthias Pöferlein (Journal of Banking and Financial Economics (JBFE), 2021)
Using the dictionary-based approach to measure the sentiment of finance-related texts is primarily focused on English-speaking content. This is due to the need for domain-specific dictionaries and the primary availability of those in English. Through the contribution of Bannier et al. (2019b), the first finance-related dictionary is available for the German language. Because of the novelty of this dictionary, this paper proposes several reforms and extensions of the original word lists. Additionally, I tested multiple measurements of sentiment. I show that using the edited and extended dictionary to calculate a relative measurement of sentiment, central assumptions regarding textual analysis can be fulfilled and more significant relations between the sentiment of a speech by a CEO at the Annual General Meeting and subsequent abnormal stock returns can be calculated.
Keywords: G12; G14; 330; Textual analysis; textual sentiment; sentiment analysis; content analysis; annual general; meeting; CEO speeches